PENGARUH PERAN SUPERVISI KEPALA SEKOLAH TERHADAP KOMPETENSI GURU DAN MOTIVASI KERJA GURU SERTA IMPLIKASINYA TERHADAP KINERJA GURU (Survey pada Guru-guru Ekonomi pada SMK Negeri di Kabupaten Kuningan) - Wijaya, Santy (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2021)
Abstract Background of the research is begun from the low quality of teachers’ competence and motivation. This may be the cause of teachers’ performance which is low and lower. Therefore the research is done to find out the influence of headmaster supervision on teachers’ motivation and competences and its implementation on teachers’ performance. The method used in this study was correlation-descriptive design. The population was all Economy teachers in all state vocational high schools in Kuningan, West java, namely 55 teachers from nine state vocational high schools in Kuningan. The instrument was questionnaires using Likert scale with five options. The technique used in analyzing the data was path analysis. All analysis and calculations was done by SPSS Program version 20.0. The result of the study were: (1) Headmaster Supervision has a positive influence on Teacher’s Performance with number of coefficient 0,101 (2) Teacher’s Competence has no significant influence on Teacher’s Performance with number of coefficient 0,360 (3) Teacher’s Motivation has no significant influence on Teacher’s Performance with number of coefficient 0,157 (4) Headmaster Supervision has a positive influence on Teacher’s Competence with number of coefficient 0,451, (5) Headmaster Supervision has a positive influence on Teacher’s Performance with number of coefficient 0,101 (2) Teacher’s Competence has no significant influence on Teacher’s Performance with number of coefficient 0,360 (3) Teacher’s Motivation has no significant influence on Teacher’s Performance with number of coefficient 0,157 (4) Headmaster Supervision has a positive influence on Teacher’s Competence with number of coefficient 0,451, (5) Headmaster Supervision has no significant influence on Teacher’s Motivation with number of coefficient 0,220.In short, this study reveals that Headmaster Supervision has an important role in improving teacher’s competence and give a good impact on teacher’s performance. Therefore, it is recommended that the headmaster should do some training in supervision to improve the quality of their leadership. Key words: Supervision; Teachers’ Competence; Teachers’ Motivation; Teachers’ Performance